Paradoxes of implementing digital manufacturing systems: A longitudinal study of digital innovation projects for disruptive change - Lukas Moschko; Vera Blazevic; Frank T. Piller (Journal of Product Innovation Management, 2023)
Digital manufacturing technologies offer many opportunities for established companies to innovate. They promote data-driven gains in operational efficiency and enable the transformation of current business models or the creation of entirely new differentiation opportunities. However, many digital innovation projects in manufacturing fall short of their initial ambitions and result in incremental improvements to an existing manufacturing system, if at all. To understand the reasons for the discrepancy between initial ambitions and achieved outcomes, we conduct a longitudinal qualitative study based on a collaborative research project with eight companies and additional expert interviews. Applying a paradox lens, we identify three tensional knots that reveal interrelated, multiple tensions of digital innovation management projects in established manufacturing firms: (1) amalgamating physical and digital assets, (2) innovating in an existing modus operandi, and (3) integrating internal and external stakeholders. These tensions result in the simultaneous occurrence of dynamic and conflicting forces that turn digital innovation projects in manufacturing away from their high initial ambitions. Our findings explain why digitizing the manufacturing system is a non-trivial endeavor for established firms, which need to balance the complexities inherent in digitization efforts and manage conflicting goals. For managers, the findings provide ways to manage the interrelated tensions in their digital innovation efforts, enabling them to better capitalize on disruptive innovation ambitions.
Keywords: 650; digital innovation management; digital manufacturing; digital transformation; Industry 4.0; paradox theory